Utilidad del índice dedo-brazo e índice tobillo-brazo en la detección temprana de arteriopatía periférica en pacientes diabéticos tipo 2. - Montaño Salinas, Aldo Amed (2016)
Type 2 diabetes mellitus is one of noncommunicable diseases most prevalent worldwide causing multiple complications such as peripheral arterial disease, which increases the risk of claudication, ischemia and lower limb amputation. Being a silent and asymptomatic disease, often diagnosed late. For this reason the use of ankle-brachial index (ABI) was raised and index finger-arm (IDB) to determine the degree of peripheral arterial obstruction, relationship between these two methods and useful for predicting PAD. The study was not experimental type, transversal, descriptive, correlational and causal-field, held in Saraguro with a sample of 50 participants, during May 2014 to November 2015. Data collection was by filling out a form collection of personally identifiable data, history, clinical evaluation, physical examination and measurement of systolic blood pressure in the arm, ankle and big toe to calculate the ITB and IDB. The results were 46% men and 54% of covered women between the age of 51-80 years, 60% of patients who had a normal ABI (1.3 to 0.9), 22% had peripheral arterial disease (EAP) mild (<0.9-0.7), 12% EAP moderate (<0.7 to 0.5), 2% EAP severe (<0.5) and 4% a suggestive ITB arterial calcification (≥1,4) .As the IDB, 68% of patients had a normal IDB (> 60) and 32% was pathological (≤ 60). The relationship between ITB-IDB showed a positive linear correlation (0.39998137) between the two variables disappears when there is arterial calcification. The usefulness of the IDB and ITB for early diagnosis of peripheral arterial disease were 94% and 99% respectively. Keywords: Type 2 diabetes mellitus, peripheral arterial disease, ankle-brachial index, toe-brachial index